Campaign of measurements to probe the good performance of the new array FARCOS for spectroscopy and correlations. (July 2016) - Acosta, L.; Andolina, R.; Auditore, L.; Boiano, C.; Cardella, G.; Castoldi, A.; D'Andrea, M.; De Filippo, E.; De Luca, S.; Dell'Aquila, D.; Francalanza, L.; Gnoffo, B.; et al.
Abstract: During the last four years, several measurements have been carried out where the capabilities of FARCOS array were tested. In some of this occasions, FARCOS was coupled to the 4π array CHIMERA, permanently placed at INFN-Laboratori Nazionali del Sud, Catania in order to be tested in real experimental measurements. At the present situation, the FARCOS demonstrator is formed by 4 telescopes out of the originally 20 that will constitute the final array. Here are presented some preliminary results obtained with the new array, probing its qualities and showing the effectiveness of FARCOS telescopes. The initial encouraging results support the construction of the complete array.